Invasive Aspergillosis in Pediatric Oncology Patients: A Rare Event With Poor Prognosis – Case Analysis to Plan Better Targeted Prophylactic or Therapeutic Measurement - Babor, F.; Schuster, F.; Mackenzie, C.; Meisel, R.; Schaper, J.; Sabir, H.; Siepermann, M.; Wessalowski, R.; Janßen, G.; Borkhardt, A.; Laws, H.-J. (Klinische Pädiatrie, 2012)
Despite the implementation of new antifungal drugs, invasive aspergillosis (IA) still remains a considerable challenge in pediatric oncology with a severe mortality. Prophylactic and therapeutic measurement have to be evaluated in these rare but poor prognostic patients. Therefore the entire group of patients at risk of developing IA has to be defined before cooperative prospective trials. In a retrospective analysis including all our patients with malignancies we looked for patients with proven/probable IA. Cases of the period from 2003 to 2008 were analyzed in detail.In the period between 2003 to 2008 24 of 755 patients were affected by proven/ probable IA. Compared to former studies incidence increased from 1.3%in 1980 to 3.4% in 2008. AML patients with or without allogeneic/haploidentical stem cell transplantation were at highest risk (24% and 25% respectively, in comparison to 1% in ALL-patients). Survival after 2 years was 50% for patients with AML and IA. In patients with high risk to develop IA the effect of intensified, intravenous antimycotic prophylaxis has to be proven prospectively in a cooperative and randomized setting.
Keywords: Aspergillosis; acute leukemia; children; fungal infection